In Vitro Genotoxic Effects of Sarcocystis gigantea Cystizoites Acetone Powder Extract on Sheep Lymphocytes - Bayati, Saad M H (The Iraqi Journal of Veterinary Medicine, 2021)
The toxin of the protozoan intracellular parasite of sheep Sarcocystis gigantea is associated with many clinical and pathological signs. The aim of the study was to investigate In Vitro various chromosomal aberrations due to sarcocystosis infection. Macrocysts of Sarcocystis gigantea were isolated from local karadi sheep, homogenized with glass Dounce homogenizer; acetone powder was prepared from it and used in various concentrations to investigate the chromosomal aberration in vitro against sheep lymphocytes. The direct effects of parasite cystizoites acetone powder revealed various genotoxicity effects. These effects included chromosomal aberration (Isogap, Breaks and Dicentrics) and chromatids aberration (Gap and Deletion). It had also an effect on the mitotic index of the lymphocyte cells division. These genotoxicities were studied for the first time with in vitro technique using sheep lymphocytes. These results reflected that Sarcocystis gigantean parasite could cause structural and internal aberration in the chromosomes of their hosts.